Evaluasi Inovasi Penyelenggaraan Ujian Dan Penilaian Online Pada Balai Diklat Keagamaan Denpasar Tahun 2018: Evaluation Of Innovation In On-line Examination And Assessment At Religious Education And Training Centre Of Denpasar In 2018 - Sugeng Sudarsono (Balai Diklat Keagamaan Denpasar, 2019)
Penelitian ini adalah penelitian evaluatif dengan model CIPP bertujuan untuk menjelaskan kualitas inovasi penyelenggaraan ujian dan penilaian online pada Balai Diklat Keagamaan Denpasar tahun 2018. Hasil analisis data menunjukkan kualitas inovasi penyelenggaraan ujian dan penilaian online pada Balai Diklat Keagamaan Denpasar tahun anggaran 2018 ditinjau dari komponen context berada dalam kategori baik atau positif dengan frekuensi skor standar ≥ 50 yaitu f(+) = 9 > f(-) = 7. Kualitas inovasi penyelenggaraan ujian dan penilaian online ditinjau dari komponen input berada dalam kategori positif atau baik dengan frekuensi skor standar ≥ 50 yaitu f(+) = 86 > f(-) = 53. Kualitas inovasi penyelenggaraan ujian dan penilaian online ditinjau dari komponen process berada dalam kategori positif atau baik dengan frekuensi skor standar ≥ 50 yaitu f(+) = 11 > f(-) = 5. Kualitas penyelenggaraan inovasi penyelenggaraan ujian dan penilaian online ditinjau dari komponen product berada dalam kategori positif atau baik dengan frekuensi skor standar ≤ 50 yaitu f(+) = 70 < f(-) = 53. Kualitas penyelenggaraan inovasi penyelenggaraan ujian dan penilaian online pada Balai Diklat Keagamaan Denpasar tahun anggaran 2018 ditinjau dari komponen context, input, process, dan product adalah pada kategori positif atau baik. Dengan demikian dapat disimpulkan bahwa inovasi penilaian online pada Diklat Tenaga Teknis Keagamaan Balai Diklat Keagamaan Denpasar Tahun 2018 pada kategori sangat baik. This study was evaluative research with CIPP model, with purposed to explain the quality of innovation in conducting on-line examinations and assessments at Religious Education and Training Centre of Denpasar in 2018. The results of data analysis showed the quality of the implementation of on-line examinations and assessments at Religious Education and Training Centre of Denpasar in 2018 in terms of components context were in the good or positive category with a standard frequency score of ≥ 50 which was f (+) = 9> f (-) = 7. Quality of innovation administering the test and online assessment in terms of Input components were in positive or good category with the standard score frequency ≥ 50, namely f (+) = 86> f (-) = 53. Quality of innovation in administering examinations and on-line assessments in terms of components processes were in positive or good category with a standard score of ≥ 50 ie f (+) = 11> f (-) = 5. Quality of implementation innovation in conducted examinations and on-line evaluations in terms of product components in positive or good category with a standard frequency score of ≤ 50 which was f (+) = 70 <f (-) = 53. Quality of implementation of innovation holding examinations and on-line evaluations in Denpasar Religious Education and training center on 2018 in terms of context components, input, the process, and the product were in the positive or good category. Thus it can be conclude that the innovation of online assessment on Training Technical Staff of Religious Education and training Center of Denpasar on 2018 in excellent category